Should the reader really pay no attention to the stage directions supplied in the translations of Ancient Greek tragedies? (The case of Aeschylus' Oresteia in Polish renditions) - Bibik, Barbara (Polskie Towarzystwo Filologiczne i Uniwersytet Wrocławski, 2019)
Some scholars claim that neither the reader nor the stage director should pay any attention to the stage directions supplied in modern renditions of ancient Greek tragedies because there were none in the Greek originals. Such an attitude, they claim, will get both the reader and the stage director closer to the interpretation intended by the author of the play in question. But is it really that simple? In my paper I would like to focus on the stage directions supplied by Polish translators of Aeschylus’ Oresteia as a vehicle for the translators’ alleged interpretation, the staging plan designed in a rendition, and the history of classical scholarship, and thus to show that when paying some attention to them, both the reader and the stage director may find relevant, interesting or unexpected information there.
Keywords: ancient greek tragedy; Aeschylus; translation